ROMANTIC MEANINGS OF THE NATIONAL AND UNIVERSAL TENDENCIES IN THE SONATA FOR VIOLIN AND PIANO BY SABIN DRAGOI - FLOREA, AUGUSTINA (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică, 2020)
The sonata for violin and piano of the remarkable Romanian composer, musicologist and folklorist Sabin Drăgoi presents an important stage in the evolutionary paradigm of the respective genre in the Romanian compositional creation of the first half of the 20th century, being highly appreciated by the award of the State Prize. Applying as an uplifting pillar the „G. Enescu romanticism” with his own harmonious fusion of the national and universal language, the author of the Sonata manifests his inclination towards universality by approaching the musical images of the romantic lineage. But, at the same time, in this creation a wide and multi-faceted exploitation of the peasant musical folklore is realized, the improvisatory manner of the popular instrumentalism and the orchestral structure of the folk music bands are reproduced, the style of the "fairy tale” narration of the quasi-speaking recitative and the characteristic features peculiar to the lyrical song are reinterpreted.